The effects of an oral MCT-based supplementation on athletic performance and energy metabolism - Niessen, M.; Hartmann, U.; Sasse, B.; Paulet, R.; Mester, J. (Book of abstracts of the 6th annual congress of the European College of Sport Science, 15th congress of the German Society of Sport Science. Cologne, 24-28 July 2001, 2001)
In einem Experiment mit 17 männlichen und weiblichen Leichtathleten wird festgestellt, dass eine MCT-Supplementierung von ca. 13 g, ca. 92 % Fett und 4 % CHO, 30 min vor Belastung, zu einer Verbesserung der individuellen Ausdauerleistung und einem Anstieg der Ermüdungsabwehr führen kann.